THE The Influence of Workload, Employee Compensation, And Employee Competence on Employee Performance at The Simpang Tiga Redelong District Court And The Simpang Tiga Redelong Syar’iyah Court, Bener Meriah Regency, Aceh Province - Dedi Alnando; Kosasih; Vip Paramarta (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of workload, employee compensation, and employee competence on employee performance at the District Court of Simpang Tiga Redelong and the Syar’iyah Court of Simpang Tiga Redelong, Bener Meriah Regency, Aceh Province. The number of research samples was determined using the Slovin formula, resulting in 53 respondents from the total population of employees. The research method applied a quantitative approach with multiple regression analysis conducted through SPSS version 16.0. Descriptive analysis revealed that the workload variable was categorized as low, while employee compensation, employee competence, and employee performance were categorized as good. The simultaneous test (F-test) produced an F-value = 9.546 with a significance level of 0.000 < 0.05, indicating that workload, employee compensation, and employee competence collectively have a significant effect on employee performance. However, the partial test (t-test) showed varying contributions of each variable. The workload variable (BK) obtained a t-value of -0.953 with sig. 0.345 (> 0.05), meaning it had no significant effect on performance. The employee compensation variable (KSP) had a positive and significant effect with a t-value of 2.436 and sig. 0.019 (< 0.05). Meanwhile, the employee competence variable (KMP) showed a positive but not significant effect with a t-value of 1.679 and sig. 0.100 (> 0.05). Based on these findings, it is suggested that institutions should pay greater attention to balanced workload distribution, strengthen a fair and performance-oriented compensation system, and continuously foster employee competence development to enhance the long-term performance of judicial institutions.